Evaluating the Effectiveness of New Criteria for Early Detection of the Start and Intensity of Influenza Epidemics in Russian Federation - L. S. Karpova; M. Yu. Pelikh; K. M. Volik; N. M. Popovtseva; T. P. Stolyarova; D. A. Lioznov (Эпидемиология и вакцинопрофилактика)
Relevance. During the COVID-19 pandemic, an early determination of the start of the influenza epidemic by the incidence of influenza and SARS in total is impossible, due to the similarity of the clinical picture of SARS and lung cases of COVID-19.Aim. The goal is to calculate and test new criteria for early detection of the start of influenza epidemics and their intensity for each of the cities–reference bases (61) of the 2 WHO National Influenza Centers based on the incidence of clinically diagnosed influenza.Tasks. To evaluate the effectiveness of baseline influenza incidence and epidemic intensity thresholds for the general population and age groups of each city in the epidemic of 2022–2023. To give a retrospective assessment of the effectiveness of influenza baselines for cities, compared with the baselines of the corresponding Federal Districts, for the seasons from 2009 to 2022. To estimate the intensity of epidemics by influenza incidence over the previous epidemies of the pandemic cycle of influenza A/California/H1N1/ virus.Materials and methods. By the 2022–2023 season. baseline lines and thresholds of influenza incidence intensity were calculated using the method of moving epidemics according to clinical diagnostic data not only for federal districts, but also for each of the observed cities (61). The calculation of the baselines was carried out according to the data of the computer database of the Influenza Research Institute on the incidence of influenza by age groups in each city over the previous 5 years in the season from 2016–2017 to 2021–2022.Results. In the 2022-23 season application of new criteria for the start of epidemics (prev.- and post-epidemic baseline influenza incidence) and their intensity revealed: early onset of the influenza epidemic (07–13.11 2022); simultaneous onset in all children's age groups; geographical spread of the epidemic in federal districts; intensity of the epidemic in the general population and age groups. The thresholds for the intensity of influenza morbidity made it possible to clarify the intensity levels of influenza epidemics from 2009 to 2023 and to show that the pandemic cycle of the influenza A(H1N1) virus continues. A comparison of the effectiveness of urban baselines with federal ones in the epidemic of 2022–2023 showed that urban baseline flu incidence lines revealed the start of epidemics 1–3 weeks earlier: among the general population in 12 cities, persons over 15 years old – in 9, children 3–6 years old – in 6 and 7–14 years old – in 5. A retrospective assessment of the effectiveness of city and federal influenza baselines (from 2009 to 2022) showed their effectiveness both in the seasons from 2009 to 2016 (before the baseline calculation period) and after. The effectiveness of urban baselines for early detection of the start of epidemics depended on the etiology of the epidemic – more with influenza A(H3N2) than with influenza A(H1N1), the level of intensity of influenza diseases and the age group of the population (more in children with low intensity and in adults with an average level).Conclusion. The results obtained on the basis of population epidemiological data on the incidence of influenza, namely, new criteria for detecting the start of an epidemic in cities, can be used in health management bodies in cities and subjects of the Russian Federation for early detection of epidemics and management decisions, timely introduction of anti-epidemic measures, creating a stock of medicines. The expected effect of the method of early epidemiological diagnosis of epidemics is a decrease in morbidity, etc.